THE EFFECT OF YOUTUBE VIDEOS IN IMPROVING STUDENTS’ LEARNING INTEREST AT SMP NEGERI 1 WATAMPONE - Rishanda, Raihan; Abduh, Amirullah; Fauzan, Muhammad Miftah (JTechLP: Journal of Technology in Language Pedagogy, 2026)
This study investigates the effect of YouTube videos as a learning media in improving students’ learning interest at SMP Negeri 1 Watampone. The method used is quantitative, utilizing a pre-experimental design. The research involved 27 students from class IX CIBI, with data collected through pre- and post-questionnaires administered before and after a four-meeting intervention using YouTube videos from February to March 2025. The study employed a quantitative approach, with data analyzed using descriptive statistics and a paired samples t-test via SPSS v.25.0. Findings revealed a significant increase in students’ learning interest, with the mean score rising from 66.1852 (high category) in the pre-questionnaire to 80.1481 (high, approaching very high) in the post-questionnaire, and a p-value of 0.000 (< 0.05), leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). The results indicate that YouTube videos significantly improve students’ learning interest by fostering engagement, attention, participation, and feelings of pleasure. This study underscores YouTube as an effective educational tool to address the limitations of traditional teaching methods, offering practical implications for teachers to integrate multimedia into English instruction and suggestions for future research to explore additional educational outcomes.